Stability Analysis, Numerical and Exact Solutions of the (1+1)-Dimensional NDMBBM Equation - Yokus, Asif; Sulaiman, Tukur Abdulkadir; Gulluoglu, Mehmet Tahir; Bulut, Hasan (E D P Sciences, 2018)
A newly propose mathematical approach is presented in this study. We utilize the new approach in investigating the solutions of the (1+1)-dimensional nonlinear dispersive modified Benjamin-Bona-Mahony equation. The new analytical technique is based on the popularly known sinh-Gordon equation and a wave transformation. In developing this new technique at each every steps involving integration, the integration constants are considered to not be zero which gives rise to new form of travelling wave solutions. The (1+1)-dimensional nonlinear dispersive modified Benjamin-Bona-Mahony is used in modelling an approximation for surface long waves in nonlinear dispersive media. We construct some new trigonometric function solution to this equation. Moreover, the finite forward difference method is utilized in investigating the numerical behavior of this equation by taking one of the obtained analytical solutions into consideration. We finally, give a comprehensive conclusions.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS